Philosophie der Republik - Stekeler-Weithofer, Primin (2018)
The freedom potential of modern societies, above all the justification of political authority, is today linked to a democratically constituted order. What is meant by the idea of being democratic seems, however, to be anything but clear. Is it only a question of representing the people through elections, ballots, and political parties, or does it include institutional culture, the division of powers, and the legal regime within a community? A "philosophy of the republic", as developed in this volume's contributions, shows that the current "dominance of the democratic" falls short of accounting for the independent significance to the republican self-organisation of state and society.